(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2011)
If there is any single popular art form that can be considered the most significant in the representation of postcolonial life in Nigeria today, it is, without question, Nollywood. Nollywood has become the most popular medium of entertainment and like Nigerian literature it plays an important role in articulating cultural and national consciousness. Although, the enterprise continues to defy definition because its production remains localized, it has become so popular among the people, considering the fact that Nigeria is now more of a watching society to a reading one. This essay examines the role of women in evangelical films in Nollywood. The films make it apt that women are very powerful tool for proselytizing, but they are also portrayed as agents of destruction employed by marine spirits and the world of the coven to wreak havoc and pain on man. Invariably, the essay articulates the strategies filmmakers employ to give expression to the notion that women are objects and not subjects in these films. High Way to the Grave and End of the Wicked are the filmic texts purposively selected for analysis.